The Principles of the Trilogy of Justice and the Principle of Aanmaning Perspectives The Binding Power of Court Decisions: The Principles of the Trilogy of Justice and the Principle of Aanmaning Perspectives The Binding Power of Court Decisions - Made Suka Dwiputra (Focus Journal : Law Review, 2022)
The principle of the Judicial Trilogy which is simple, fast and low cost is one of the principles in civil procedural law applicable in Indonesia. Court decisions that have permanent legal force are not always the final result of a case or dispute if the losing party does not want to carry out the contents of the decision voluntarily. lose in a case to carry out the contents of the decision voluntarily. The formulation of the problem raised is the binding power of court decisions in unlawful acts and is also viewed from the perspective of the trilogy of justice principle and the principle of security. This study uses a normative legal research type, which is to examine and analyze legal materials and issues based on statutory regulations. In this case, whether the judicial institution in the aanmaning process does not become a juridical problem of the conflict between the trilogy of justice principles and the aanmaning in the judiciary. In the discussion, the theory of the legal system, the theory of legal certainty, the theory of authority and the theory of legal protection are used in order to be able to reach the description of what should be done in the future.